2022
DOI: 10.3390/agronomy12112894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyacinth Treatment by Hydrogen Peroxide Stabilized with Silver and Some Fungicides on the Fungal Infection of Substrate and Bulbs and on Plant Growth and Development

Abstract: The aim of the study was to demonstrate the feasibility of using hydrogen peroxide stabilized with silver (H2O2-Ag+) and selected fungicides for the treatment of hyacinth bulbs and to determine their effects on the development of fungi colonizing the substrate and bulbs and their impact on plant growth and development. Hydrogen peroxide stabilized with silver (H2O2-Ag+) and captan, pyraclostrobin + boscalid and methyl thiophanate + tetraconazole were used to treat hyacinth bulbs before planting, in the form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the case of the spider mite inhabiting chrysanthemum leaves, the pest was found dead as early as 6 minutes after spraying the plants with Huwa San TR-50 at a concentration of 0.1% (unpublished data). Wojdyła et al (2022) showed that immersion of hyacinth tubers before planting stimulated their growth and development.…”
Section: In Disinfection Of Surfaces and Storage Chambersmentioning
confidence: 99%
“…In the case of the spider mite inhabiting chrysanthemum leaves, the pest was found dead as early as 6 minutes after spraying the plants with Huwa San TR-50 at a concentration of 0.1% (unpublished data). Wojdyła et al (2022) showed that immersion of hyacinth tubers before planting stimulated their growth and development.…”
Section: In Disinfection Of Surfaces and Storage Chambersmentioning
confidence: 99%